2021
DOI: 10.5897/ajmr2020.9443
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of virulent and antibiotic resistant Staphylococcus species in ready-to-eat Rhynchophorus phoenicis and Archachatina marginata vended along the Port Harcourt-Bayelsa route

Abstract: This study was aimed at determining the occurrence of Staphylococcus species in ready-to-eat (RTE) Rhynchophorus phoenicis (edible larvae) and Archachatina marginata (land snail) vended along Port Harcourt-Bayelsa route. Eighty samples from four locations were analysed employing standard techniques for proximate and microbiological analyses; virulence determination and antibiotic susceptibility. Data were statistically analyzed using ANOVA and t-test. The mean proximate results revealed the presence of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
1
1
1
Order By: Relevance
“…The polymerase chain reaction results for detection of the virulence genes sea and seb in S. aureus showed that all S. aureus strains did not possess both virulence genes. The result from this study is in contradiction to the finding of Ngoka et al (2021) who reported presence of sea and seb genes in S. aureus strains isolated from readyto-eat Rhynchophorus phoenicis and Archachatina marginata vended along the Port Harcourt-Bayelsa route. The PCR result for amplification of the aggR, eaeA and astA virulence genes showed that aggR had the highest prevalence of 4 (28.58%) positives, followed by astA, 3 (21.44%) while eaeA had the lowest of 14.29%.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The polymerase chain reaction results for detection of the virulence genes sea and seb in S. aureus showed that all S. aureus strains did not possess both virulence genes. The result from this study is in contradiction to the finding of Ngoka et al (2021) who reported presence of sea and seb genes in S. aureus strains isolated from readyto-eat Rhynchophorus phoenicis and Archachatina marginata vended along the Port Harcourt-Bayelsa route. The PCR result for amplification of the aggR, eaeA and astA virulence genes showed that aggR had the highest prevalence of 4 (28.58%) positives, followed by astA, 3 (21.44%) while eaeA had the lowest of 14.29%.…”
Section: Discussioncontrasting
confidence: 99%
“…These can be administered for treatment of Staphylococcus mediated illness. The S. aureus strains were 100% resistant against augmentin, cloxacin and ceftadizine This is in agreement with previous study by Ngoka et al (2021). Other studies have reported higher resistance to gentamycin and ofloxacin by different microorganisms (Afolabi et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation